(untitled) (International journal of medical sciences, 2025)
The article explains the scientific significance of treating bacterial eye infections. Topical problem in ophthalmology is currently more bacterial than keratitis of cornea ulcers. It is connected with progressive increase in the irncidence of this pathology.